White paper defining optimal palliative care in older people with dementia: A Delphi study and recommendations from the European Association for Palliative Care. (March 2014) - van der Steen, Jenny T; Radbruch, Lukas; Hertogh, Cees MPM; de Boer, Marike E; Hughes, Julian C; Larkin, Philip; Francke, Anneke L; Jünger, Saskia; Gove, Dianne; Firth, Pam; Koopmans, Raymond TCM; Volicer, Ladislav; et al.
Background: Dementia is a life-limiting disease without curative treatments. Patients and families may need palliative care specific to dementia. Aim: To define optimal palliative care in dementia. Methods: Five-round Delphi study. Based on literature, a core group of 12 experts from 6 countries drafted a set of core domains with salient recommendations for each domain. We invited 89 experts from 27 countries to evaluate these in a two-round online survey with feedback. Consensus was determined according to predefined criteria. The fourth round involved decisions by the core team, and the fifth involved input from the European Association for Palliative Care. Results: A total of 64 (72%) experts from 23 countries evaluated a set of 11 domains and 57 recommendations. There was immediate and full consensus on the following eight domains, including the recommendations: person-centred care, communication and shared decision-making; optimal treatment of symptoms and providing comfort (these two identified as central to care and research); setting care goals and advance planning; continuity of care; psychosocial and spiritual support; family care and involvement; education of the health care team; and societal and ethical issues. After revision, full consensus was additionally reached for prognostication and timely recognition of dying. Recommendations on nutrition and dehydration (avoiding overly aggressive, burdensome or futile treatment) and on dementia stages in relation to care goals (applicability of palliative care) achieved moderate consensus. Conclusion: We have provided the first definition of palliative care in dementia based on evidence and consensus, a framework to provide guidance for clinical practice, policy and research.